Results from the Belgian mantle cell lymphoma registry. Issue 3 (4th May 2017) - Vergote, Vibeke; Janssens, Ann; André, Marc; Bonnet, Christophe; Van Hende, Vanessa; Van Den Neste, Eric; Van Eygen, Koen; Maerevoet, Marie; Pranger, Delphine; Schroyens, Wilfried; Debussche, Sarah; Maertens, Vincent; et al.
Abstract : Introduction: Mantle cell lymphoma is a B-cell non-Hodgkin's lymphoma characterized by a t (11;14), resulting in overexpression of cyclin D1. Conventional chemotherapy obtains frequent (but short) remissions, leading to a poor median overall survival (OS) of 3–5 years. To obtain more information about the prevalence and current treatment of Mantle cell lymphoma (MCL) in Belgium, we collected data in a Belgian registry of MCL. Materials and methods: All Belgian MCL patients, t (11;14) and/or cyclin D1 positive, seen in hematology departments over a one-year period (April 2013–March 2014) were included. Data about patient characteristics, histology, treatment lines, and response were compiled and retrospectively analyzed. Results: Four hundred and four patients were included with a median age at diagnosis of 64 years (range 23–96 years) and a male predominance (72%). For 2013, we calculated a prevalence of at least 36.2 per million and an incidence of at least 7.0 per million in the Belgian population. Characteristics at diagnosis involved lymphadenopathy (82%), splenomegaly (44%), B-symptoms (39%), and hepatomegaly (10%). Bone marrow invasion was present at diagnosis in 77%. Stage at diagnosis was advanced in the majority of cases. The median number of treatment lines was 1. Type of first line treatment included a combination of anthracyclin and cytarabine-based regimen (34%), anthracyclin (39%), and other. Rituximab was used in 88% of first line treatments. In 44% first line treatment was followed by autologous stem cell transplantation. Conclusion: The analysis of this Belgian MCL registry provides insight in the epidemiology, demographics, and current treatment of our Belgian MCL population.